Transformasi Manajemen Layanan Pendidikan Nonformal melalui Pendekatan Data-Driven OEE: Perspektif Manajemen Strategis - Masduki Asbari (Journal of Information Systems and Management (JISMA), 2025)
This study analyzes the operational effectiveness of private tutoring services by adapting the Overall Equipment Effectiveness (OEE) concept from the manufacturing sector to non-formal education. A descriptive qualitative research design with a case study was conducted on 20 students during one operational period; data were collected through observations of learning activities, schedule documentation, and learning evaluation records. The results showed Availability of 90%, Performance of 89%, and Quality of 90%, resulting in a total OEE value of 72%. This figure indicates that service effectiveness is relatively good but still far from the world-class measure often emphasized in the OEE literature for educational services, which generally ranges around 85% or more, thus providing room for concrete improvement. The novelty of the study lies in adapting the OEE concept to non-formal educational services, specifically private tutoring, making it a data-driven operational measurement tool that can be operated by PNFI managers for continuous improvement. Practically, these findings encourage increased data-driven schedule planning, pedagogical competency enhancement, learning differentiation, and the implementation of a performance dashboard to encourage evidence-based corrective actions. The main research questions answered are how OEE adapted from TPM can operationally measure the effectiveness of private tutoring services in non-formal education; what sources of time loss (waste) affect Availability and Performance; how instructional differentiation and teacher capacity building are related to quality improvement; and how the use of performance dashboards and learning analytics strengthens data-driven decision-making for service quality improvement.